2015
DOI: 10.1111/coa.12391
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative changes in telemetry measurements after cochlear implantation and its impact on early activation

Abstract: Based on the results in this study, an earlier activation can be recommended. This will shorten the time the patient needs to wait following cochlear implantation, and rehabilitation can begin sooner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Traditionally, the earliest activation time was 4 to 6 weeks after surgery. However, various studies investigating early activation have been published and shown the safety, feasibility and residual hearing preservation [912, 18, 19]. Early activation within 24 hours after surgery has been reported by our hospital [9, 12] and others [10].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Traditionally, the earliest activation time was 4 to 6 weeks after surgery. However, various studies investigating early activation have been published and shown the safety, feasibility and residual hearing preservation [912, 18, 19]. Early activation within 24 hours after surgery has been reported by our hospital [9, 12] and others [10].…”
Section: Discussionmentioning
confidence: 87%
“…This suggests a delicate balance between cell cover formation, a divergence effect with electrical stimulation, and pro- and anti-fibrotic cytokines [29]. The further evolution of impedance after 2 months has been reported in several studies with no significant changes in adults [8, 15, 18, 19]. …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…If the coil magnet has sufficient coupling with the implant, swelling of the wound is not a contraindication to early fitting, but it should be taken into account (e.g., checking the magnet strength). In the study by Wolf-Magele et al [2015], there was also a dropout of an EF patient (dropout rate 0.2%) because early fitting was not possible due to the wound healing status. As in other studies [Marsella et al, 2014;Hagr et al, 2015;Batuk et al, 2019;Sun et al, 2019], the current manuscript also showed that early fitting of the sound processor was feasible and safe for the majority of patients.…”
Section: Feasibility and Safetymentioning
confidence: 99%
“…In the past, a standard healing period of 3-6 weeks occurred after CI surgery before the sound processor was activated for the first time [Hagr et al, 2015;Zeh and Baumann, 2015;Hoppe et al, 2017;Lenarz, 2017]. This relatively long waiting period was scheduled to ensure adequate wound healing and to prevent infections of the skin flap [Alsabellha et al, 2014;Marsella et al, 2014;Vaerenberg et al, 2014;Wolf-Magele et al, 2015]. In recent years, the surgical technique and instruments have been continuously developed.…”
Section: Introductionmentioning
confidence: 99%